PENGARUH INFORMASI AKUNTANSI DALAM BENTUK MANAJEMEN LABA UNTUK PENGAMBILAN KEPUTUSAN INVESTASI - QIVTIA, MARIA (Jurnal Akuntansi AKUNESA, 2018)
This study examines the effect of accounting information in the lines of earnings management proxied by the value of discretionary accrual using the formula modified jones model on investment decision making proxied with stock return. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange. Selection of sample using purposive sampling technique during research period, year 2014-2016. Data were analyzed using linear regression. The results showed that earnings management has a positive effect on stock returns, if the value of discretionary accrual in a company rises then the stock return will also rise. Levels in samples that perform positive earnings management at levels one and two have no effect, whereas at level three positively affects. While the level on the sample that performs negative earnings management does not affect the stock return.